2016
DOI: 10.3390/toxics4040025
|View full text |Cite
|
Sign up to set email alerts
|

Association of Long-Term Pesticide Exposure and Biologic Parameters in Female Farm Workers in Tanzania: A Cross Sectional Study

Abstract: Abstract:The study aimed to assess the association of long-term pesticide exposure (≥5 years) with hematological, serum biochemical parameters and acetylcholinesterase activity in farm workers. These pesticides included organophosphorus pesticides, carbamates, pyrethroids, dithiocarbamates, and other pesticides such as endosulfan. Applying a cross-sectional study design, 69 females from a pesticide-exposed farm population and 30 females from a district not using pesticides (reference group) were studied. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 60 publications
(75 reference statements)
1
17
1
2
Order By: Relevance
“…Many of our results were consistent with those reported by others among pesticide-exposed individuals compared to controls, such as: increased levels of Hb, HCT, RBC [67]; increased lymphocyte, monocyte and platelets counts [68,70,72]; reduced mean neutrophil counts, serum acetylcholinesterase activity and T4 [70]. Evidence from some animal studies were also consistent with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…Many of our results were consistent with those reported by others among pesticide-exposed individuals compared to controls, such as: increased levels of Hb, HCT, RBC [67]; increased lymphocyte, monocyte and platelets counts [68,70,72]; reduced mean neutrophil counts, serum acetylcholinesterase activity and T4 [70]. Evidence from some animal studies were also consistent with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…The result of present study is in accordance with previous studies done by Gomes et al (1997) . [14][15][16][17][18] On the other hand, this result is not coinciding with the finding of study done by Shadnia et al 2005. [19] This inconsistency may be due to the differences in amount of dosage or duration of exposure.…”
Section: Discussioncontrasting
confidence: 64%
“…Another study reported a stronger link between indoor pyrethroid exposure and autism spectrum disorder in the children of mothers who received less folic acid during pregnancy than those who received more (183). In a cross-sectional study of female farm workers in Tanzania, occupational exposure to pesticides affected haematological and biochemical parameters such as haematocrit, red cell corpuscular volume, serum glutamic oxaloacetate transaminase, and esterase (184). One case of pyrethroid skin necrosis was reported in a 67-year old diabetic woman suffering from delusions of parasitosis (185).…”
Section: Human Exposure To Pyrethroidsmentioning
confidence: 99%